Introduction: the military commissions saga - Abrams, Norman (Journal of international criminal justice, 2010)
One of the key reasons why the Bush Administration opted to create the military commissions for trying terrorism cases was the desire to use classified information without having to face the risk that in some instances the government might be faced with a dilemma whether to reveal the classified information or drop the prosecution and free the defendant. The editorial comments published in this issue of the Journal challenge the provisions of the Military Commissions Act (MCA) 2006 under the law of war, international law, the Geneva Conventions as well as under US constitutional law. In the end, however, the legal status of the MCA will be finally determined by the US Supreme Court. It seems likely that a new majority of the Court would be formed that would uphold the constitutionality of many of the provisions of the MCA. The US approach to dealing with terrorism has consisted of a series of acts, both on the world stage and in the United States, in a continuing drama. If the events of the post-9/11 period are thought of in terms of high theatre, then the link between Hamdan and the MCA moves us into a state of dramatic tension the Court first resolves a series of key issues, then Congress moves centre stage and on most of the issues takes contrary positions, but in a context where the Court itself has invited legislative action. The denouement will be reached when these issues return to the Supreme Court and it then decides whether the statutory provisions in question are constitutionally vulnerable